2017
DOI: 10.23917/jramathedu.v1i2.3720
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Students’ Difficulties in Solving Story Based Problems and Its Alternative Solutions

Abstract: This study aims to analyze the students’ difficulties of MTs Negeri Surakarta 1 in solving story based problems on the subject of Pythagoras along with its alternative solutions. This is a qualitative descriptive research. This study illustrates the difficulties of students in solving story based problemsof the subject of Pythagoras. Research subjects in this study is composed of three students of class IX with each capable of high, medium and low. The data collection was condducted using the test method and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
(1 reference statement)
1
5
0
2
Order By: Relevance
“…Besides, the subject slightly underst ood the learning content related to the topic. This statement is in line with Rachmawati (2017) and Widyastuti et al (2017) that low-ability students have difficulty creating mathematical modeling of a problem. Students do not use all given information, confuse in determining the problem-solving strategy, and are unable to perform mathematical procedures.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Besides, the subject slightly underst ood the learning content related to the topic. This statement is in line with Rachmawati (2017) and Widyastuti et al (2017) that low-ability students have difficulty creating mathematical modeling of a problem. Students do not use all given information, confuse in determining the problem-solving strategy, and are unable to perform mathematical procedures.…”
supporting
confidence: 88%
“…Meanwhile, Rachmawati (2017) revealed that alternative solutions for low-ability students are by providing an in-depth understanding of the concept and insight into issues in the form of word problems by carefully teaching them to understand the problem given.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, students' error in determining the mathematical model of a problem only proved that their transformation skills were still low. Rachmawati (2016), Jupri and Drijvers (2016) stated that one of the constraints the students experienced in solving mathematics is the difficulty in developing the mathematical model. This should be used as a reflection for math teachers to improve the forthcoming math teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Problems in learning are the core issues of education and learning problems as the main activities in education (Rachmawati, 2017). Kereh, Sabandar, and Tjiang in Dirgantoro (2019) state that difficulties in learning mathematics can occur at any level of education.…”
Section: Introductionmentioning
confidence: 99%